THE EFFECT OF SCHOOL HEADS' LEADERSHIP STYLE ON LEARNERS' PERCEPTION OF SCHOOL CLIMATE - Simbre, Abegail P.; Buenaventura, Ma. Laarni D.; Aquino, John Michael; Vera, Jayson L. de; Vera, Mary Grace D. de (Jurnal Aplikasi Manajemen, 2023)
A positive school climate and excellent leadership are essential to promote holistic school administration and high-quality education. Researchers wanted to find out how school leaders' leadership styles affect the perception of students in a high-quality educational environment using a mixed-method research design. A total of 1018 people participated in this survey, including 907 students and 111 school officials from 24 different schools. The Multifactor Leadership Questionnaire (MLQ) was used to determine the most common leadership style among school heads. The SCAI Secondary General Version was used to assess students' perceptions of the school climate level. Also, four school principals participated in one-on-one interviews on how their leadership styles changed during the pandemic. All aspects of school climate, including community relations, student interactions, learning and assessment, physical appearance, discipline environment, attitude, and culture, had high levels of perceived school climate. Results show that transformational leadership, contingent reward, management by exception, and inspirational motivation are the most prevalent styles of leadership, while laissez-faire, idealized influence, and intellectual stimulation are the least prevalent. Only two out of forty-two (42) correlations between school atmosphere and leadership style were significant. Student interactions and idealized influence are also included in this category. School administrators and teachers need to understand the level of transformational leadership and the school climate to create the best school environment, which will improve the quality of teaching and learning and, in the end, school performance.